Aziridine carboxylate from D-glucose: synthesis of polyhydroxylated piperidine, pyrrolidine alkaloids and study of their glycosidase inhibition - Dhavale, Dilip D.; Kumar, K. S. A.; Chaudhari, Vinod D.; Sharma, T.; Sabharwal, Sushma G.; PrakashaReddy, J. (Organic & Biomolecular Chemistry, 2005)
The D-glucose derived aziridine carboxylate 5 was obtained from (E)-ethyl-6-bromo-1,2-O-isopropylidene-3-O-benzyl-5-deoxy-alpha-D-xylo-5 -eno-heptofuranuronate 4 through conjugate addition of benzylamine and in situ intramolecular nucleophilic expulsion of bromine. The regioselective aziridine ring-opening, using water as a nucleophile, resulted in the alpha-hydroxy-beta-aminoester 6, which was exploited in the synthesis of six and five membered azasugars 1b/1c and 2b/2c, respectively The glycosidase inhibitory activity of the title compounds was evaluated.